The Influence of Education and Training on Management Students' Interest in a Career in Agribusiness: A Questionnaire Approach - Malau, Grace; Siregar, Zulkarnain; Khairani, Disa; Fadilla, Siti; Khairiyah, Najmah (Holistic Science, 2024)
The agricultural sector is one of the key sectors in the global and national economy. In Indonesia, agricultural activities include various agricultural production, processing, marketing and distribution activities. One group that is expected to make a significant contribution to the development of the agricultural sector is management students. However, in reality management students' interest in a career in agriculture is relatively low. This research aims to determine the influence of education and training on interest in a career in agribusiness among management students using quantitative methods with a survey approach. The research results show that education and training have a significant simultaneous influence on career interest in agribusiness. These findings also show that education and training explain 15. 8% of the variation in career interest, while the remaining 84. 2% is influenced by other factors not included in the study. Although significant effects were found, the ability of education and training to explain variability in career interests is still limited. This study highlights the need for further research to explore additional factors influencing career interest in agriculture among management students.